WACANA PEMBERLAKUAN UNDANG-UNDANG DARURAT SIPIL DALAM SITUASI WABAH COVID-19 SERTA DAMPAK EKONOMI DI INDONESIA - Anto Kustanto (Fakultas Hukum Universitas Wahid Hasyim, 2020)
This study aims to discuss the urgency of the enactment of the civil emergency law in responding to the covid-19 pandemic. Economic and sociological factors considerations were raised in this study, although they remained in the juridical corridor. This research is a normative legal research, using the law approach and conceptual approach. This research concludes that the status of civil emergency has a number of consequences in accordance with Government Regulation in Lieu of Law or Perpu Number 23 of 1959 concerning Revocation of Law Number 74 of 1957 and Establishing Dangerous Conditions. The enactment of the Civil Emergency Law can limit people's movements in activities that will have a negative impact on the economy